1995
DOI: 10.1177/014572179502100607
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs About Exercise Among Persons With Non-Insulin-Dependent Diabetes

Abstract: This study examined attitudes and beliefs about exercise among 83 persons with non-insulin-dependent diabetes who had completed outpatient diabetes counseling. An adaptation of the Health Belief Model, labeled the Exercise Behavior Model, guided perceptual measures. Fifty-two percent of the subjects were exercising 3 or more days per week. Those with a greater length of time since diabetes counseling were more likely to be currently exercising. Positive and negative attitudes toward exercise characterized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 13 publications
2
49
0
2
Order By: Relevance
“…7,23,24 The physical activity adherence rate in some studies varied between 37 and 52%. 20,25 The rates of regular visits to a physician, physical exercise and foot care were low in the study group (Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…7,23,24 The physical activity adherence rate in some studies varied between 37 and 52%. 20,25 The rates of regular visits to a physician, physical exercise and foot care were low in the study group (Table 3).…”
Section: Discussionmentioning
confidence: 96%
“…Researchers have identified that exercise non-adherence is linked to factors such as time and convenience (Glasgow et al, 1997;Swift, Armstrong, Beerman, Campbell, & Pond-Smith, 1995), fear of complications and discomfort (Swift et al, 1995), and feelings of futility (Glasgow et al, 1997). Environmental factors such as weather condition affects whether an individual will continue with an exercise program (Swift et al, 1995).…”
Section: Self-regulation Behaviormentioning
confidence: 99%
“…Predictors for inactivity include negative attitude towards exercise like physical discomfort or illness, lack of family and social support, lack of confidence and time, depression and environmental barriers [89][90][91][92]. These findings' validity is supported by researchers who also reported that self-efficacy and family supports are important predictors for performing physical exercise [76,[93][94][95][96].…”
Section: Confounders For Physical Activity Self-carementioning
confidence: 84%